Faster acquisition of laparoscopic skills in virtual reality with haptic feedback and 3D vision. Issue 5 (3rd September 2017) - Hagelsteen, Kristine; Langegård, Anders; Lantz, Adam; Ekelund, Mikael; Anderberg, Magnus; Bergenfelz, Anders
Abstract: Background: The study investigated whether 3D vision and haptic feedback in combination in a virtual reality environment leads to more efficient learning of laparoscopic skills in novices. Material and methods: Twenty novices were allocated to two groups. All completed a training course in the LapSim ® virtual reality trainer consisting of four tasks: 'instrument navigation', 'grasping', 'fine dissection' and 'suturing'. The study group performed with haptic feedback and 3D vision and the control group without. Before and after the LapSim ® course, the participants' metrics were recorded when tying a laparoscopic knot in the 2D video box trainer Simball ® Box. Results: The study group completed the training course in 146 (100–291) minutes compared to 215 (175–489) minutes in the control group ( p = .002). The number of attempts to reach proficiency was significantly lower. The study group had significantly faster learning of skills in three out of four individual tasks; instrument navigation, grasping and suturing. Using the Simball ® Box, no difference in laparoscopic knot tying after the LapSim ® course was noted when comparing the groups. Conclusions: Laparoscopic training in virtual reality with 3D vision and haptic feedback made training more time efficient and did not negatively affect later video box-performance in 2D.